Expanding application of the voussoir beam analog to horizontally bedded and passively bolted flat-roof excavations using the discrete element method. (December 2021) - Abousleiman, Rami; Sinha, Sankhaneel; Walton, Gabriel
Abstract: The voussoir beam analog is a well-established analytical method that has been successfully applied to the design of flat-roof excavations in discontinuous rockmasses. However, application of voussoir beam theory is limited to very specific conditions. Previous authors have attempted to account for more realistic loading and geometric conditions, but have not presented systematic or verified methods to account for variations in inelastic material behavior or supported roof geometry. This study presents multiple original numerical models that methodically assess the effects of increasing material and geometric complexity on voussoir beam mechanical behavior and develops adjustments to the Diederichs & Kaiser (1999) analytical solution to account for variations in post-peak material behavior and the interactions between multiple passively bolted layers. A step-by-step guide is presented for implementing these adjustments.